Sense of well-being indicators: attachment to public parks in Putrajaya, Malaysia - Ujang, Norsidah; Moulay, Amine; Zakariya, Khalilah (Elsevier, 2015)
In Malaysian urban areas, the issue of underutilization of public parks persists despite the apparently well-designed landscape. Face to face interviews with 30 park users in SaujanaHijau Park (SP) and Putra Perdana Park (PP) in Putrajaya were conducted to examine the role of place attachment in park utilization and social interaction. The study found that frequent visits, proximity to residences, and the landscape features contribute to the development of attachment to a place. Despite the meaningful experience with nature and green environment, the function of the park as a social space for the community was still insufficient. Engagement to the parks was dominated by personal health-related activities while social interaction involved mainly family members and close friends. This situation limits the function of public parks as social integrators.